Interactive Techniques in Grid Computing: A Survey - Rosmanith, Herbert; Volkert, Jens (Computing and Informatics, 2012)
In Grid computing, the dominating paradigm is batch processing. Grid middleware ships with batch-job support only, while lacking support for interactive applications. The reason is that grid middleware was developed for computation-intensive jobs, which may run for a long time before a result becomes available. This leads to a ``post-mortem'' approach of analysing the output, possibly resulting in a waste of computing and research time. Adding the possibility to observe and steer the job during execution enables the researcher to modify job-parameters without restarting the entire job. In this paper, several interactivity support techniques are explored, followed by several examples proving their usefulness.